Buga (Bugar Dengan Toga) untuk Meningkatkan Derajat Kesehatan Keluarga - Sholihatil Hidayati; Susanti, Dhina Ayu (Jurnal Pengabdian Masyarakat (JUDIMAS), 2023)
ABSTRAK Imunitas tubuh sangat penting untuk menanggulangi wabah penyakit . Kita harus mencegah masuknya mikroorganisme penyebab penyakit ke dalam tubuh kita, diantara dengan cara mencuci tangan menggunakan sabun dengan air mengalir, menggunakan masker, physical distancing, dan yang paling penting adalah menjaga dan meningkatkan imunitas tubuh dengan baik sehingga tubuh menjadi lebih kuat dan tidak mudah terserang penyakit. Tanaman Obat Keluarga (TOGA) menjadi komoditas yang banyak dicari masyarakat pasca-merebaknya Covid-19. TOGA dipercaya berkhasiat meningkatkan daya tahan tubuh atau imunitas sebagai penangkal Covid-19. Tujuan pengabdian ini adalah melakukan penyuluhan pemanfaatan Tanaman Obat Keluarga (TOGA) Untuk meningkatkan imunitas tubuh menghadapi Pandemi Covid-19 di Perumahan Griya Mangli RT 03/RW 18 Kabupaten Jember dan menyediakan tanaman obat. Metode yang digunakan adalah penyuluhan dan praktek lapangan. Target yang diharapkan adalah Ibu-ibu di perumahan Griya Mangli memiliki pengetahuan tentang jenis TOGA dan manfaatnya. Hasil yang telah dicapai melalui program kegiatan ini sesuai dengan target yang telah direncanakan sebelumnya yaitu: penyuluhan terkait pemanfaatan TOGA serta praktek penanaman TOGA di lahan kosong milik warga. Kesimpulan dari pengabdian kepada masyarakat (PKM) ini bahwa setelah kegiatan PKM ibu-ibu di RT 03 RW 18 Perumahan Griya Mangli semakin peduli terhadap kesehatan dan mampu memanfaatkan TOGA untuk menangkal penyakit dan meningkatkan imunitas tubuh. Kata Kunci : PKM, Penanaman, Penyuluhan, TOGA ABSTRACT The body's immunity is very important to overcome disease outbreaks. We must prevent the entry of disease-causing microorganisms into our bodies, including by washing hands with soap with running water, using masks, physical distancing, and the most important thing is to maintain and enhance the body's immunity properly so that the body becomes stronger and less susceptible to infection. disease. Family Medicinal Plants (TOGA) have become a commodity that is much sought after by the public after the outbreak of Covid-19. TOGA is believed to be efficacious in increasing the body's resistance or immunity as an antidote to Covid-19. The purpose of this service is to conduct counseling on the use of Family Medicinal Plants (TOGA) to increase body immunity against the Covid-19 Pandemic at Griya Mangli Housing RT 03/RW 18 Jember Regency and provide medicinal plants. The method used is counseling and field practice. The expected target is that mothers in Griya Mangli housing have knowledge about the types of TOGA and its benefits. The results that have been achieved through this activity program are in accordance with the previously planned targets, namely: counseling related to the use of TOGA and the practice of planting TOGA on vacant land owned by residents. The conclusion from this community service (PKM) is that after the PKM activities the women in RT 03 RW 18 Griya Mangli Housing are increasingly concerned about health and are able to use TOGA to ward off disease and increase body immunity. The results that have been achieved through this activity program are in accordance with the previously planned targets, namely: counseling related to the use of TOGA and the practice of planting TOGA on vacant land owned by residents. The conclusion from this community service (PKM) is that after the PKM activities the women in RT 03 RW 18 Griya Mangli Housing are increasingly concerned about health and are able to use TOGA to ward off disease and increase body immunity. The results that have been achieved through this activity program are in accordance with the previously planned targets, namely: counseling related to the use of TOGA and the practice of planting TOGA on vacant land owned by residents. The conclusion from this community service (PKM) is that after the PKM activities the women in RT 03 RW 18 Griya Mangli Housing are increasingly concerned about health and are able to use TOGA to ward off disease and increase body immunity. Keywords: PKM, Planting, Counseling, TOGA